The effect of intensive tens therapy on muscle blood biomarkers and activities of daily living in haemorrhagic stroke patients: a preliminary study - Jee, See Heng (2021)
Stroke, in particular haemorrhagic stroke, is a highly debilitating condition with several rehabilitations’ problems. Transcutaneous Electrical Nerve Stimulation (TENS) has long been an indispensable tool in stroke rehabilitation. Thus, this study aimed to discern the effects of TENS, specifically intensive TENS therapy for 2 weeks, on a motor-impaired haemorrhagic stroke patient’s recovery, on top of 6 weeks of conventional physiotherapy. We want to elucidate the effect of TENS and conventional physiotherapy on serum Creatine Kinase and serum Troponin T, as the roles of each biomarker is unclear in informing the outcome of stroke rehabilitation. Our outcome measures were serum Creatine Kinase, serum Troponin T, and modified Barthel Index scores. This was a pre-post convenient sampling controlled interventional study, conducted in the Department of Neurosciences and Rehabilitation Medicine Unit of Hospital Universiti Sains Malaysia, with 10 control subjects and 10 TENS-therapy subjects. 1 of the 10 interventional subjects decided to withdraw from the study due to health issues, while another 2 interventional subjects and 1 control subject were lost to follow up. The intervention group underwent both intensive TENS therapy and conventional physiotherapy for 2 weeks, then 4 weeks of conventional physiotherapy. The control group underwent 6 weeks of conventional physiotherapy. All three outcome measures of each participant were measured before and after 2 weeks of intensive TENS therapy and 6 weeks of conventional therapy. We then compared and analysed the pre and post values for significance. Results indicated that serum Creatine Kinase and serum Troponin T were relatively unaffected by 2 weeks of intensive TENS therapy and 6 weeks of conventional physiotherapy (serum Creatine Kinase: p = 0.521) (serum Troponin T: p = 0.632). The same also applied to 6 weeks of conventional physiotherapy alone (serum Creatine Kinase: p = 0.572) (serum Troponin T: p = 0.921). On the contrary, modified Barthel Index score comparisons did show significant increases in intervention group (p = 0.040) as compared to control group. This study currently acts as a pilot study and the results of this study, which demonstrated no change in blood biomarkers but improved activity of daily living scores in haemorrhagic stroke patients post-ITT, shall be treated as preliminary results for future research on intensive TENS therapy.